A short remark on He's frequency formulation. Issue 2 (June 2021) - Liu, Caixia
The unprecedented frequency formulation proposed by Chinese mathematician, Ji-Huan He, has been caught much attention due to its extreme simplicity and remarkable accuracy for nonlinear oscillators. This short remark uses an example without a linear term arising in ball-bearing oscillating to show its effectiveness and reliability.